Qualitative Characterization of Fat Fraction from Crunchy Cereal Products Available on the Polish Market - Górska, Agata; Brzezińska, Rita; Bryś, Joanna; Ostrowska-Ligęza, Ewa; Dolatowska-Żebrowska, Karolina; Wirkowska-Wojdyła, Magdalena; Przybyłowska, Aleksandra (Polish Journal of Natural Sciences, 2023)
The paper presents the qualitative assessment of fat isolated from the selected crunchy cereal products available on the Polish market. The samples were characterized by determination of the fatty acids composition and distribution in triacylglycerol structure. Additionally, oxidative stability was identified. To estimate the quality of the fat, the acid value and the peroxide value were also determined. The results showed that the tested products were a good source of monounsaturated and polyunsaturated fatty acids, especially oleic and linoleic acid. Analyzed products showed statistically different resistance to oxidation. The longest time of oxidation induction was determined in the case of fat extracted from crunchy cereal bar covered with chocolate, while the shortest for the fat extracted from crunchy breakfast cereals with chia seed. The analysis of the peroxide and the acid values did not show any abnormalities regarding the quality of the fat tested.